La grieta del espectáculo: juventud shuar, comunicación e insurgencia tecnológica territorial [Dossier: Comunicación comunitaria, mediaciones digitales y soberanía tecnológica] - Rivas Moreno, Diego José (2026)
This article examines the configuration and meanings of the communicative practices of youth from the Shuar Arutam People in the Ecuadorian Amazon, within a context defined by the expansion of the digital regime, the coloniality of development, and territorial disputes. Moving beyond a conception of technology as a technical or neutral phenomenon, the study investigates its symbolic, affective, and political dimensions through the situated uses that emerge within conflict. The research adopts a methodology of circular co-theorizing that triangulates critical discourse analysis, life stories, and an ethnographic approach, in a shared inquiry process that enables thinking from the territory, rather than about it. Fieldwork was conducted between December 2024 and March 2025 in the canton of Tiwintza, with particular attention to the tensions youth navigate between memory, connectivity, and technological reappropriation. The corpus integrates institutional, corporate, and media discourses, alongside experiential narratives and ethnographic records gathered in community spaces. The findings reveal that, far from passively reproducing digital devices, the youth deploy creative uses that reconfigure their meaning, transforming them into tools for mutual care and identity affirmation. From these margins, communication ceases to be a mere channel and becomes a space for dispute, world-making, and the everyday practice of sovereignty. The article provides key insights for rethinking the relationship between technology, power, and resistance from a Southern epistemic perspective, anchored in the body, language, and collective ways of inhabiting the present.